Predicting Mobile Game Adoption: Integrating Game Features and Theory of Planned Behavior - Mohammad Rizal Gaffar; Wahyu Rafdinal; Eko Susanto; Cahaya Juniarti (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2022)
This study investigates gamers' behavior in adopting mobile games by integrating game features and the theory of planned behavior (TPB).  This study used 408 samples of Indonesian gamers. A partial least square is applied to examine the influence among subjective norm, perceived behavioral control, attitude, game features, and intention to play mobile games. The results show that the integration between Game features and TPB gives a deeper explanation of gamers' behavior in adopting mobile games. Considering the factors in gamers' behavior, this study's results give the base to formulate an implementation strategy for the appropriate game features in attracting gamers' interest to keep playing mobile games. It is also the first study that integrates Game features and TPB to assess mobile game adoption.